2022
DOI: 10.1055/s-0042-1757618
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Stalk Hemangioblastoma: Complete Resection through Orbitozygomatic Approach with Extradural Anterior Clinoidectomy

Abstract: Background Pituitary stalk hemangioblastomas (PSHBLs) are rare vascular tumors and their surgical removal is challenging due to the proximity with several fundamental anatomic structures including the pituitary stalk, third ventricle, hypothalamus, and optic pathways. To date, only few descriptions of transcranial and transsphenoidal approaches for PSHBLs have been reported in the literature and none in video, with suboptimal outcomes in terms of pituitary function preservation. Here, we describe the use of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The typical vascular flow void signal was shown in patient 2, which is a low signal on T2 MRI and postcontrast enhancement. In addition, by analyzing the surgical resection degree of supratentorial tumors, we found that the total resection of cystic tumors located in the cerebral lobe could be easily performed, while for sellar tumors, whether cystic or solid type, the total resection of GTR was more difficult to perform compared with that of the other parts ( 29 ). Therefore, it is suggested that both cystic and solid tumors in the sellar region should be inspected before surgery to evaluate whether they can be completely resected.…”
Section: Discussionmentioning
confidence: 99%
“…The typical vascular flow void signal was shown in patient 2, which is a low signal on T2 MRI and postcontrast enhancement. In addition, by analyzing the surgical resection degree of supratentorial tumors, we found that the total resection of cystic tumors located in the cerebral lobe could be easily performed, while for sellar tumors, whether cystic or solid type, the total resection of GTR was more difficult to perform compared with that of the other parts ( 29 ). Therefore, it is suggested that both cystic and solid tumors in the sellar region should be inspected before surgery to evaluate whether they can be completely resected.…”
Section: Discussionmentioning
confidence: 99%